Ribifolin, an orbitide from jatropha ribifolia, and its potential antimalarial activity - Pinto, Meri Emili F. [UNESP]; Batista, Joao M. [UNESP]; Koehbach, Johannes; Gaur, Pratibha; Sharma, Abhinay; Nakabashi, Myna; Cilli, Eduardo Maffud [UNESP]; Giesel, Guilherme M.; Verli, Hugo; Gruber, Christian W.; Blanch, Ewan W.; Tavares, Joseam F.; et al. (Amer Chemical Soc, 2015)
A new orbitide named ribifolin was isolated and characterized from Jatropha ribifolia using mass spectrometry, NMR spectroscopy, quantitative amino acid analysis, molecular dynamics/simulated annealing, and Raman optical activity measurements and calculations. Ribifolin (1) and its linear form (1a) were synthesized by solid-phase peptide synthesis, followed by evaluation of its antiplasmodial and cytotoxicity activities. Compound 1 was moderately effective (IC50 = 42 mu M) against the Plasmodium falciparum strain 3D7.